Моделирование электропривода электромобиля с системой рекуперации энергии на базе суперконденсатора - Бушер, Виктор Владимирович; Герасимяк, Валдис Георгиевич (НТУ "ХПИ", 2013)
Described the possibility of using supercapacitors in the electric drive with the battery. Proposed structural diagram of electric drive and according model in the MatLab Simulink. Were obtained transient processes diagrams in electric drive in modes acceleration-braking.
Keywords: современное электромобилестроение; автономные электротранспортные средства; применение суперконденсаторов; аккумуляторные батареи; система MatLab Simulink; режим разгон-торможение